Amorphous martensite in β-Ti alloys - Long Zhang (Nature Portfolio, 2018)
Displacive martensitic transformations through lattice distortion usually involve a change from one crystal structure to another. Here however, the authors “melt” metastable Ti alloys during cooling and show that a martensitic transformation can lead to the formation of an intragranular amorphous phase.